Causes and Consequences of Losses in the Water Supply System of Cement Manufacturing Enterprises - Abilov, Elyor Ermamatovich (European Journal of Life Safety and Stability (2660-9630), 2022)
The article mainly cites the example of the water supply system in cement plants and the main water consumers Sherabad Cement Plant. Information is provided on losses that occur during the water supply process at the enterprise and are not taken into account. The formation of small cracks in the trench of the primary water supply route, the seasonal nature of the faults observed during the year, the amount of water losses not taken into account, the timing of the emergency response. In the analysis of the results, accidents in the waterway trench from well №5 to the main pumping station occur mainly during the rainy months, the main cause of failure is the sand layer, which should protect the pipeline from external influences. It is concluded that due to the nature of moisture is absorbed into the soil. It was also reported that it would take some time to detect water leaks from small cracks in the pipeline as a result of the accident, and that the company was incurring significant costs for annual repairs. At the end of the article, scientific recommendations are given as a solution to this problem.